Morfometria de núcleos de células tumorais no diagnóstico diferencial da doença de Marek e leucose linfóide - Leal, Valdiana Araújo (2003)
Marek's disease and lymphoid leukosis are avian lymphoid tumors, caused by viruses, causing great economic losses in the poultry industry. This work aimed to make the differential diagnosis between these two neoplasms more objective and easy with the use of computerized morphometry of the tumor cell nuclei. Ten slides from each neoplasm were analyzed by nuclear measurement, 50% spleen and 50% liver, confirmed positive by histopathological examination. The measured parameters were area, perimeter and sphericity of 50 cores in each slide analyzed. The greater dispersion of data obtained in Marek's disease, objectively confirmed the greater pleomorphism of the cells of this disease compared to Lymphoid Leukosis. The data obtained during the measurement were subjected to canonical discriminant analysis, building discriminant functions for diagnosis in the liver, spleen and both. The three functions proved to be effective in the identification of different tumor cells, however, when the organ used was the spleen, greater efficiency was achieved. Similarly, lymphoid leukosis is more easily identified.